Characterization and evaluation of a novel O-carboxymethyl chitosan films with Mimosa tenuiflora extract for skin regeneration and wound healing - Valencia-Gómez, Laura-Elizabeth (2019)
In this study, films of O-carboxymethyl chitosan with Mimosa tenuiflora extract were manufactured, characterized, and evaluated. In this work, both the synthesis of O-carboxymethyl chitosan and the extraction of the active ingredient of Mimosa tenuiflora extract from the cortex are described. First, the extract of Mimosa tenuiflora in water was obtained by precipitation with ethanol, filtering, and concentrating. Subsequently, a study was conducted of scratch wound healing to determine the optimal concentration of extract to be used in the manufacture of films. The produced O-carboxymethyl chitosan films and the Mimosa tenuiflora extract were mixed, and their chemical composition, tensile properties, and wettability were characterized by Fourier-transform infrared spectroscopy, mechanical tests, and contact angle measurement. The antimicrobial properties of the films were tested by turbidimetry using two types of bacteria. In addition, a study of the enzymatic degradation of the films with the enzyme lysozyme was performed. Finally, in vitro studies to assess the biocompatibility and cytotoxicity of films with fibroblastic cells were carried out as well as the kinetic analysis of healing in mice. It was found that the addition of Mimosa tenuiflora extract in the polymer matrix of the films made with O-carboxymethyl chitosan improves the proliferation of fibroblast and accelerates wound healing, thus providing a novel biomaterial for skin regeneration.